Novel Reusable Software Components for Fault Tolerant Architecture - Banothu, Lalu; Mohan, M. Chandra; Kumar, C. Sunil (International Journal of Advanced Science and Technology, 2019)
The emergence of component and distributed computing technologies paved way for software engineering discipline to explore reusable software components to expedite development, reduce software development cost and effort. Many component technologies such as Distributed Component Object Model (DCOM), Enterprise Java Beans (EJB) and Common Object Request Broker Architecture (CORBA) came into existence. Many real world applications are built using the reusable components. However, the problem identified in the recent state-of-the-art is that it is very challenging problem to have fault tolerance as the components may run in different machines across the globe. Therefore there is need for a framework with fault tolerant architecture for design of reusable components in software engineering. The aim of this paper is, therefore, to investigate the present state of the art of fault tolerant architectures that provide fault tolerance to applications that make use of reusable components in distributed environment. Keywords – Component based software engineering (CBSE), components, reusability, fault tolerant architectures.